Comparison of Conventional and Contextual Mathematics Learning in Elementary Schools - Presty Rumani, Risza (PT. Anagata Sembagi Education, 2025)
Mathematics learning at the elementary school level plays a strategic role in developing students' logical and critical thinking skills from an early age. However, the conventional approach still dominant in many schools tends to emphasize procedural solutions without building in-depth conceptual understanding. This approach risks separating mathematics from students' real-life contexts. As an alternative, the contextual teaching and learning (CTL) approach has emerged as a model that emphasizes the connection between material and students' everyday experiences. This study aims to compare the two approaches through a literature review method with a descriptive qualitative approach. Data were collected from various accredited academic sources over the past five years. The analysis results indicate that the conventional approach is effective in developing procedural skills, while the contextual approach excels in fostering conceptual understanding, learning motivation, and 21st-century skills. However, CTL requires teacher preparedness and adequate resources. This study recommends an adaptive integration of the two approaches to create more relevant, inclusive, and contextual mathematics learning strategies. The theoretical and practical implications point to the importance of constructivism as the primary foundation in developing meaningful mathematics teaching strategies in elementary schools.